The Purga Project: Indigenous Knowledge Research - Sheehan, Norm; Walker, Polly (The Australian Journal of Indigenous Education, 2001)
We are Indigenous University lecturers involved in research with the Purga Elders and Descendants Aboriginal Corporation. Our research at Purga involves the instigation of Indigenous Knowledge as the basis of effective and valid research methodologies. This article will describe the work that the University of Queensland (UQ) Aboriginal and Torres Strait Islander Studies Unit is doing at Purga. It will then articulate the principles of Indigenous Knowledge Research that inform this work.